THU0035 Cytokine production by cd3+ t cell in synovial fluid from patients affected by psoriatic arthritis and rheumatoid arthritis. (1st June 2001) - Riente, L; Pratesi, F; Frigelli, S; Sedie, A Delle; Scavuzzo, M; Chimenti, D; Migliorini, P
Abstract : Background: Psoriatic arthritis (PsA) is an inflammatory arthropathy associated with psoriasis, characterised by synovitis which often leeds to destruction of cartilage and bone. The mechanism of joint damage is unclear, but it's likely that cytokines play critical roles. In PsA cytokines have been previously measured by enzyme-linked immunoassays; however, these molecules are not very stable in inflammatory fluids and are detectable only when produced in large amount. Objectives: The aim of our study was to analyse the cytokines production in synovial fluids of patients affected by psoriatic arthritis. Methods: We analysed cytokines production ex vivo by single cell analysis in flow cytometry in synovial fluids of 9 patients affected by PsA. As control group we used synovial fluids from 8 patients affected by Rheumatoid Arthritis (RA). Synovial fluid leukocytes isolated on Ficoll gradients were stimulated with phorbol-myristate-acetate and ionomycin, treated with brefeldin, permeabilized and stained with anti-CD3, anti-IL4 and anti-IFNg. Results: In 9 patients affected by PsA, IFNg-producing cells were the vast majority (43%, 46%, 75%, 55%, 51%, 42%, 38%, 32%, 20% of CD3 + cells). A similar predominance was observed in 8 patients with rheumatoid arthritis (64%, 36%, 35%, 75%, 38%, 29%, 46%, 26%). Conclusion: IFNg is the typical cytokine produced by TH1 T cells, thus the results of our study suggest that TH1 T cell selectively home to synovial tissue in PsA, as already shown in RA. A better understanding of cytokine production in psoriatic arthritis synovium in a larger number of patients may help to clarify the pathogenesis of the disease and lead to the development of more specific and effective therapeutic agents. Reference: Nuti S, Rosa D, Valiante NM, Saletti G, Caratozzolo M, Dellabona P, Barnaba V, Abrignani S. Dynamics of intra-hepatic lymphocytes in chronic hepatitis C: enrichment for Va24+ Tcells and rapid elimination of effector cells by apoptosis. Eur J Immunol. 1998;28:3448–56